Measuring, modelling and testing ozone exposure, flux and effects on vegetation in southern European conditions--what does not work? A review from Italy. - Ferretti, M; Fagnano, M; Amoriello, T; Badiani, M; Ballarin-Denti, A; Buffoni, A; Bussotti, F; Castagna, A; Cieslik, S; Costantini, A; De Marco, A; Gerosa, G; et al. (Environmental pollution (Barking, Essex : 1987), 2007)
Ozone (O3) exposure at Italian background sites exceeds UN/ECE concentration-based critical levels (CLe(c)), if expressed in terms of AOT40. Yet the occurrence of adverse effects of O3 on forests and crops is controversial. Possible reasons include (i) ability of response indicators to provide an unbiased estimate of O3 effects, (ii) setting of current CLe(c) in terms of cut-off value and accumulation level, (iii) response functions adopted to infer a critical level, (iv) environmental limitation to O3 uptake and (v) inherent characteristics of Mediterranean vegetation. In particular, the two latter points suggest that critical levels based on accumulated stomatal flux (CLe(f)) can be a better predictor of O3 risk than CLe(c). While this concept is largely acknowledged, a number of factors may limit its applicability for routine monitoring. This paper reviews levels, uptake and vegetation response to O3 in Italy over recent years to discuss value, uncertainty and feasibility of different approaches to risk assessment.
Keywords: AOTx; Critical levels; Effects; Mediterranean Region; Ozone; Stomatal flux

Modifications of the leaf surface structures of Quercus ilex L. in open, naturally CO2-enriched environments - Paoletti, E; Nourrisson, G; Garrec, J P; Raschi, A (Plant, Cell & Environment, 1998)
Two Italian CO2 springs allowed us to study the long-term effect of a 350–2600 μmol mol–1 increase in CO2 concentrations on the surface structures of leaves of Quercus ilex L. Carbon dioxide increased the quantity of cuticular waxes, above an apparent threshold of 750 μmol mol–1 CO2. Leaf wettability was not modified by CO2 concentrations. Reduction in stomatal frequency was observable up to 750 μmol mol–1 CO2, the slope being almost the same as that estimated for the increase in CO2 concentration from pre-industrial times to the present. At higher concentrations, CO2 seemed to exert no more impact on stomatal frequency.
Keywords: Elevated CO2; leaf wettability; natural CO2 spring; Quercus ilex; stomatal frequency; wax amount

O3 AND 03+C02 EFFECTS ON A MEDITERRANEAN EVERGREEN BROADLEAF TREE, HOLM OAK (QUERCUS iLEX L.) - Manes, F; Vitale, M; Donato, E; Paoletti, E (Chemosphere, 1998)
The aim of this work is to analyze the effects of a) short-term treatments with different concentrations of 0, (daily 6-hour fumigation with 0, 65, 175 and 300 ppb for 3-4 days); and 6) a medium term treatment with O9 (150 ppb three times a week for thirty days on the whole) and CO2 (700 ppm) on gas exchange, chlorophyll fluorescence, and peroxidase activity in holm oak (Quercus ilex L.) leaves. The results show that net photosynthesis, transpiration, Fv/Frvr ratio and POD activity were not influenced until an O1 concentration of 300 ppb was reached. At this threshold, significant alterations in these physiological and biochemical parameters were found. The treatment with +C02 +O, showed an increase of net photosynthesis suggesting thus an antagonistic effect of CO2 with regard to Oj-induced injuries, while CO2 alone increased photosynthesis and decreased transpiration but induced no effects on FV/‘F, ratio or peroxidase activity. From our data, holm oak shows a resistance to episodes ofphotochemical 0, stress, that in the Mediterranean region can reach peaks of > 100 ppb. This response is likely to be due to the morpho-anatomic structure of helm oak leaves and their sclerophyllous adaptations. This might leads helm oak to adopt a stress tolerance strategy with regard to leaf response to O,, the effects of which cannot be ameliorated by an increase of atmospheric CO2
Keywords: CO2 (voyant); Holm oak; Net photosynthesis; ozone exposure; peroxidase activity; Transpiration

UV-band and acid rain effects on beach ( Fagus sylvatica L.) and holm oak ( Quercus ilex L.) leaves - Paoletti, E (Chemosphere, 1998)
Beech (Fagus sylvatica L.) and holm oak (Quercus ilex L) leaves were subjected to simulated acid rain and UV-B radiation for 10 days. The almost glabrous beech leaves revealed a greater predisposition to developing macroscopic necrotic lesions than the pubescent holm oak leaves. This response is due primarily to their different morpho-anatomical structure, rather than to a difference in the synthesis of UV-B absorbing pigments (flavonoids); the response was also accompanied by microscopically observable alterations (collapse of epidermal cells, fusion of surface wax structures, structural damage to the stomata) and by the reduction of stomatal conductance
Keywords: acid rain; beech; damage; Holm oak; leaves; necrosis; stomatal conductance (voyant); uv-b radiation

The behavior of oaks in response to natural and induced exposure to the surfactant ABS - Moricca, S; Paoletti, E; Comparini, C (Ann. For. Sci., 1993)
Quercus pubescens, Q frainetto, Q ilex and Q robur were sprayed with ABS (sodium dodecyl benzenesulfonate, a surfactant often found in marine aerosols) over 2 growing seasons to test the effect of the surfactant on the leaf wax structure. Though all species were affected, they differed in their tolerance to ABS. The effect of ABS was also tested on the pollen quality of Q ilex. Pollen from declining and apparently healthy individuals was germinated in cultures with different concentrations of ABS. A negative effect on pollen germination and pollen tube length was noted. The reduction in pollen viability could affect the genetic resources of holm oak populations in the future.
Keywords: ABS; oak spp; pollen; wax structure

STOMATAL DENSITY VARIATION IN BEECH AND HOLM OAK LEAVES COLLECTED OVER THE LAST 200 YEARS - Paoletti, E; GELLINI, R (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1993)
In leaf samples of Fagus sylvatica L. and Quercus ilex L. collected over the last 200 years a reduction has been observed in the stomatal density of 43% and 28% respectively. The ecological implications, particularly concerning atmospheric CO2 increase and drought tolerance, are discussed.
Keywords: ATMOSPHERIC CO2 INCREASE; FAGUS-SYLVATICA; QUERCUS-ILEX; stomatal density

Effects of acid fog and detergents on foliar leaching of cations - Paoletti, E; GELLINI, R; Barbolani, E (Water, Air, & Soil Pollution, 1989)
Relative rates of nutrient leaching from the epygeous apparatus of Quercus ilex L., Fagus sylvatica L., Acer opalus Mill., Euonymus japonicus L. and Phaseolus vulgaris L. were examined after exposure to simulated acid fog. Copper, A1, Fe, Mn, Ca, Mg, and Pb were preferentially leached at low pH, whereas leaching rates of Na, K, and Cd did not appear to be pH-influenced. Addition of surfactant to the spray solutions showed a slight reduction of leaching for all elements investigated. Except for Mg, foliar nutrient levels were not influenced during our experiments.
Keywords: acid deposition; detergent (voyant); nutrient leaching

Elemental leaching from Quercus ilex L. in response to simulated acidic fog - Paoletti, E; Udisti, R; Pantani, F; Barbolani, E (Water, Air, & Soil Pollution, 1989)
Quercus ilex L. seedlings were intermittently exposed to simulated acidic and non-acidic fogs in 6-hr events for 16 times. After a 1-mo break, treatments were carried out again for a 5 day period. Strong acidity neutralization, weak acidity release and cation leaching from foliage and stem were determined. Leaching of AI, Cu, Mn, Fe, Cd, Pb, Ca, Mg, and K increased in response to acid treatment. This effect was less marked for Na. A positive correlation between H ÷ uptake and cation leaching was found. Cationic release and neutralization of strong acidity increased after breaks in acid treatment, but this faculty and the a m o u n t of leached cations and neutralized acidity decreased with time. The stem showed a higher cation loss and higher buffer capacity than the leaves.
Keywords: acidity; Cations (voyant); foliar leaching